Vibrational Spectroscopy - de Caro, Dominique (IntechOpen, 2012)
The infrared and Raman spectroscopy have applications in numerous fields, namely chemistry, physics, astronomy, biology, medicine, geology, mineralogy etc. This book provides some examples of the use of vibrational spectroscopy in supramolecular chemistry, inorganic chemistry, solid state physics, but also in the fields of molecule-based materials or organic-inorganic interfaces.